Spray nozzles, working pressures and use of adjuvant in reduction of 2,4-D herbicide spray drift - João D. Godinho Jr.; Lucas C. Vieira; Renato A.A. Ruas; Alberto Carvalho Filho; Vinícius R. Faria; Pedro I.V.G. God (Planta Daninha, 2020)
Abstract Background: The study of the interactions between equipment, application methods, and spray mixtures is fundamental to optimize the application of pesticides. The determination of the best combination of these factors can reduce the drift during the application of the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D). Objective: The objective this paper is to study the influence of nozzle models, working pressures, and surfactant adjuvant in reducing the drift of 2,4-D. Methods: The spectrum of nozzle drops was determined for a conventional flat jet; flat jet with air induction; double plane jet with air induction; deflector flat jet with air induction; and an empty cone with air induction at pressures of 200, 300, 400, and 500 kPa. This was quantified in a wind tunnel with four drifts: water; water + surfactant adjuvant; water + 2,4-D; and water + 2,4-D + surfactant adjuvant, applied by the five nozzle models at four working pressures. The data was evaluated by analysis of variance and, when significant, by the Tukey test and regression at 5% significance level. Results: The interactions between the nozzle models, working pressure, and spray mixture directly influenced the 2,4-D drift. Conclusions: The use of surfactant adjuvant must be carried out carefully, according to the nozzle model, working pressure, and spray mixture. The conventional single fan jet nozzle is more sensitive to increased working pressure and has a high potential to cause drift compared with the models with air induction.